WAVELET-BISPECTRUM METHOD FOR DETERMINING QRS COMPLEX POSITIONS IN ECG SIGNALS - В’юницький, Олег; Тоцький, Олександр (SWorldJournal, 2025)
The paper considers and investigates a new method for determining the positions of characteristic points of an electrocardiographic signal based on wavelet-bispectrum signal processing, which provides an increase in the probability of determining the R-c